2015
DOI: 10.1080/14681811.2015.1082070
|View full text |Cite
|
Sign up to set email alerts
|

Preventing alcohol-exposed pregnancy among American-Indian youth

Abstract: Research has determined that the prevention of alcohol-exposed pregnancies (AEP) must occur pre-conceptually with women, either by reducing alcohol intake in women planning pregnancy or at-risk for becoming pregnant, or by preventing pregnancy in women drinking at risky levels. One such AEP prevention programme with non-pregnant American Indian women is the Oglala Sioux Tribe (OST) CHOICES (Changing High-risk alcohOl use and Increasing Contraception Effectiveness Study) Programme, which shows promise in reduci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 31 publications
0
19
0
Order By: Relevance
“…There is both an epidemiological need and also a community-defined need for AEP prevention in AIAN youths. Findings from past studies cite the need for AEP prevention in youths, and the tribal community responding in this project agreed with the need for AEP prevention with AIAN youths [36]. A similar qualitative study with urban AIAN adolescents and adults also found that FASD prevention should consider cultural and community values and contexts [46].…”
Section: Discussionmentioning
confidence: 57%
See 3 more Smart Citations
“…There is both an epidemiological need and also a community-defined need for AEP prevention in AIAN youths. Findings from past studies cite the need for AEP prevention in youths, and the tribal community responding in this project agreed with the need for AEP prevention with AIAN youths [36]. A similar qualitative study with urban AIAN adolescents and adults also found that FASD prevention should consider cultural and community values and contexts [46].…”
Section: Discussionmentioning
confidence: 57%
“…The team has collaborated with this particular tribal community since approximately 2004 and has developed several community-led research interventions [44,48,49]. For this study, we used several tenants of community-based participatory research (CBPR) in that the community defined AEP prevention for youths as a need within the community [36], and we gathered vast community input through our formative qualitative work, constructing an intervention based on community-driven data. We also wanted to meet the needs of the youth population by utilizing technology to deliver the intervention.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To meet this community need, we are in the process of piloting the CHOICES intervention in a group setting, a methodology that utilizes cultural norms of group communication and provides support through group interaction [ 27 ]. Through our community engagement, we also identified a need to work with adolescents and young American Indian women to expand the population we work with, and we have applied for funding to expand to that group [ 28 ]. With this important community input and with extensive opportunities for expansion, the OST CHOICES Program will only grow in the coming years and expand to serve additional women in the movement to prevent AEP.…”
Section: Discussionmentioning
confidence: 99%